HUBUNGAN ANTARABANGSA: TEORI DAN PRAKTIS (INTERNATIONAL RELATIONS: THEORY AND PRACTICE; A REVIEW - Tumin, Makmor (Journal of Social Political Sciences, 2023)
Roy Anthony Rogers, Tunku Mohar Mokhtar and Wan Sharina Ramlah Wan Ahmad Amin Jaffri’s book "Hubungan Antarabangsa: Teori dan Praktis (International Relations: Theory and Practice" (2022) is an important contribution to understanding the dynamics of war and peace, targeting Malay readers, university students, diplomats, military and police personnel, and interested members of the public. The book provides an overview of international relations, exploring both theoretical concepts and practical applications. It cover topics such as international law, global governance, diplomacy, conflict resolution, and international security. The book may also examine the roles of different actors in the international system, including nation-states, intergovernmental organizations, non-state actors, and individuals. Overall, "Hubungan Antarabangsa: Teori dan Praktis" likely provides a comprehensive exploration of international relations, combining both theoretical frameworks and practical examples to enhance readers’ understanding of the subject.